Severity Level and Duration of Energy Deficit in Mice Affect Bone Phenotype and Bone Marrow Stromal Cell Differentiation Capacity - Avilkina, Viktorija; Leterme, Damien; Falgayrac, Guillaume; Delattre, Jérôme; Miellot, Flore; Gauthier, Véronique; Chauveau, Christophe; Ghali Mhenni, Olfa (Frontiers in Endocrinology, 2022)
Anorexia nervosa is known to induce changes in bone parameters and an increase in bone marrow adiposity (BMA) that depend on the duration and seriousness of the disease. Previous studies have found that bone loss is associated with BMA accumulation. Sirtuin of type 1 (Sirt1), a histone deacetylase that is partly regulated by energy balance, was shown to have a pro-osteoblastogenic and anti-adipogenic effects. To study the effects of the severity and duration of energy deficit related to bone loss, a mouse model of separation-based anorexia (SBA) was established. We recently demonstrated that moderate body weight loss (18%) 8-week SBA protocol in mice resulted in an increase in BMA, a bone loss and a significant reduction in Sirt1 expression in bone marrow stromal cells (BMSCs) extracted from SBA mice. We hypothesised that Sirt1 deficit in BMSCs is associated with bone and BMA alterations and could potentially depend on the severity of weight loss and the length of SBA protocol. We studied bone parameters, BMA, BMSC differentiation capacity and Sirt1 expression after induction of 4 different levels of body weight loss (0%,12%,18%,24%), after 4 or 10 weeks of the SBA protocol. Our results demonstrated that 10-week SBA protocols associated with body weight loss (12%, 18%, 24%) induced a significant decrease in bone parameters without any increase in BMA. BMSCs extracted from 12% and 18% SBA groups showed a significant decrease in Sirt1 mRNA levels before and after co-differentiation. For these two groups, decrease in Sirt1 was associated with a significant increase in the mRNA level of adipogenic markers and a reduction of osteoblastogenesis. Inducing a 18% body weight loss we tested short SBA protocol (4-week). We demonstrated that 4-week SBA protocol caused a significant decrease in Tb.Th only, without change in other bone parameters, BMA, Sirt1 expression or differentiation capacity of BMSCs. In conclusion, for the first time, this study showed that the duration and severity of energy deficit are critical for changes in bone parameters, BMSC differentiation and Sirt1 expression. Furthermore, we showed that in this context, Sirt1 expression could impact BMSC differentiation with a further effect on bone phenotype.